ANALISIS RENDEMEN PATI DARI BERBAGAI SUMBER TANAMAN LOKAL DI KALIMANTAN BARAT - Azis, Debby Febyola; Maherawati, Maherawati; Hartanti, Lucky (Fakultas Pertanian Universitas Tanjungpura, 2026)
Starch is a major plant polysaccharide widely utilized as a raw material in the food industry, making the diversification of starch sources from local plants increasingly important. One key parameter in evaluating the potential of starch sources is starch yield, which reflects both starch content and extraction efficiency. This study aimed to analyze and compare the starch yield of three local plant sources from West Kalimantan, namely breadfruit (Artocarpus altilis), purple sweet potato (Ipomoea batatas), and red rice (Oryza sativa L.). The research was conducted using a randomized block design with one treatment factor, starch source, and three replications. Starch extraction was carried out through crushing, filtration, sedimentation, drying, and sieving processes, with several method modifications. Data were analyzed descriptively using quantitative approaches. The results showed that purple sweet potato produced the highest starch yield (9.14%), followed by red rice (8.28%), while breadfruit starch showed the lowest yield (2.23%). These differences were influenced by the biological and morphological characteristics of each raw material. This study provides preliminary scientific data on the starch yield of local plant resources from West Kalimantan, contributing to the development of alternative and sustainable starch sources for food and non-food applications.